Rendimiento de camarón litopenaeus vannamei en sistemas semi-intensivos con aguas subterráneas en tierras adentro - Matute Aguirre, Luis Eduardo (2007)
The shrimp culture sector needs to optimize resourses and to sep new sourses of producción, as is the case of the cultivation of shrimp with well water in continental lands, avoiding to affect the mangrove ecosystem and therefore the shrimp grows in a media free of diseases. Due to the above mentioned facts, we have the target of determine the shrimp yielding in semi-intensive systems with well waters inland. The shrimp production with this water sources is similar to that with sea water, although its difference is referred to the size of the ponds: the sea water ponds have great size (4-20ha), meanwhile the ponds with well water are smaller (0.4-2ha), which optimizes the small area available. The main deficiency with well water is the lack of potassium, but is supplied with the addition of possium muriate until get the needed levels (not more than 50mg/l). In this trial were tested 4 stocking densities, and from the results, there were not significant statiscal differences, but as referred to size there was a numerical difference, with best development of shrimps in ponds stocked with lower densities; conversely, the ponds stocked with increased stocking density obtained a higher producction level. The survival level were similar for all treatments (71-75%).